Tourism Development Sustainable in the District South Nias: Influence Government in Increase Community Welfare - Zalukhu, Berkat Dedikasi; Sirojuzilam, Sirojuzilam; Revida, Erika; Purwoko, Agus; Charloq, Charloq (Formosa Journal of Science and Technology, 2024)
"Tourism Development Sustainable in the District South Nias: Influence Government in Increase Community Welfare " is a purposeful study For understanding How the role of government in pushing development sustainable can increase the well-being community in the Regency South Nias, North Sumatra. Sustainable development, which is purposeful For increasing the well-being of society and fulfilling the needs as well as aspirations, became the focus main of the study This Study This carried out in coastal areas of Regency South Nias, with a focus on how role of government in developing coastal and marine areas, as well impact to well-being public. The study also includes an analysis of the development strategy economy area in frame increase capacity development economy. Results study This expected can give more understanding Good about How the government can role in pushing development sustainable and improving the well-being public. Besides that, research can become a reference for government and stakeholders' interests in formulating future development policies and strategies.